The pulsating nature of large-scale Saharan dust transport as a result of interplays between mid-latitude Rossby waves and the North African Dipole Intensity. (October 2017) - Cuevas, E.; Gómez-Peláez, A.J.; Rodríguez, S.; Terradellas, E.; Basart, S.; García, R.D.; García, O.E.; Alonso-Pérez, S.
Abstract: It was previously shown that during August the export of Saharan dust to the Atlantic was strongly affected by the difference of the 700-hPa geopotential height anomaly between the subtropics and the tropics over North Africa, which was termed the North African Dipole Intensity (NAFDI). In this work a more comprehensive analysis of the NAFDI is performed, focusing on the entire summer dust season (June–September), and examining the interactions between the mid-latitude Rossby waves (MLRWs) and NAFDI. Widespread and notable aerosol optical depth (AOD) monthly anomalies are found for each NAFDI-phase over the dust corridors off the Sahara, indicating that NAFDI presents intra-seasonal variability and drives dust transport over both the Mediterranean basin and the North Atlantic. Those summer months with the same NAFDI-phase show similar AOD-anomaly patterns. Variations in NAFDI-phase also control the displacement of the Saharan Heat Low (SHL) westwards or eastwards through horizontal advection of temperature over Morocco-Western Sahara or eastern Algeria-Western Libya, respectively. The connection between the SHL and the NAFDI is quantified statistically by introducing two new daily indexes that account for their respective phases (NAFDI daily index -NAFDIDI-, and SHL longitudinal shift index -SHLLSI-) and explained physically using the energy equation of the atmospheric dynamics. The Pearson's correlation coefficient between the one–day-lag SHLLSI and the NAFDIDI for an extended summer season (1980–2013) is 0.78. A positive NAFDI is associated with the West-phase of the SHL, dust sources intensification on central Algeria, and positive AOD anomalies over this region and the Subtropical North Atlantic. A negative NAFDI is associated with the East-phase of the SHL, and positive AOD anomalies over central-eastern Sahara and the central-western Mediterranean Sea. The results point out that the phase changes of NAFDI at intra-seasonal time scale are conducted by those MLRWs that penetrate deeply into the low troposphere. Graphical abstract: Highlights: Saharan dust transport out of Africa shows a pulsed behaviour. The North African Dipole Intensity (NAFDI) modulates Saharan dust export. NAFDI intra-seasonal variations are driven by mid-latitude Rossby waves. NAFDI drives the temporal evolution of the Saharan Heat Low longitudinal shift. NAFDI may modulate dust emission in central-western Sahara.